Posterior Reversible Encephalopathy Syndrome Induced by an Acute Postinfectious Glomerulonephritis - Jamal Ouachaou; Ilyass Laaribi; Mohammed Maarad; Ikram Zaid; Rajae Alkouh; Houssam Bkiyar; Brahim Housni (Hindawi Limited, 2021)
Posterior reversible encephalopathy (PRES) is a rare but a serious disease that affects the central nervous system. PRES is responsible for various but nonspecific neurological symptoms, including confusion, coma, and seizures as well as visual disturbances. Diagnosis is made using cerebral MRI which typically shows at the early stage, bilateral symmetrical parietooccipital hyperintensities on T2 and fluid-attenuated inversion recovery (FLAIR) sequences. Case study. In this article, we base our research on a case study that includes, as a population sample, a 9-year-old boy who suffers from an acute postinfectious glomerulonephritis and arterial hypertension. Two days before diagnosis, he developed confusion with generalized tonic-clonic attacks. His blood pressure was 180/80 mmHg. A cerebral computed tomography made in emergency showed cerebral edema. It was supplemented by magnetic resonance imaging which revealed cortical and posterior cortical lesions which appear as hypointense on T1 and hyperintense on T2 and Flair. An MRI control was performed 40 days later which shows a clear improvement of the occipital lesions. PRES is a radioclinical syndrome characterized by the association of variable neurological signs which reversibility is conditioned by the early diagnosis and the correction of the contributing factors.